Estimating the national logistics outsourcing market size: a multi-method approach and an application to the Italian context. Issue 7 (29th April 2021) - Prataviera, Lorenzo Bruno; Tappia, Elena; Perotti, Sara; Perego, Alessandro
Abstract : Purpose: Today logistics is an ever-growing multi-billion-dollar business, and logistics operations have been increasingly outsourced to specialised players. The intended aim of this paper is to offer a multi-method approach for estimating the size of the national logistics outsourcing market by building upon financial-reporting data of logistics service providers (LSPs). Design/methodology/approach: The proposed approach is structured into four steps, clustered around two main stages: framework setting and data collection, and processing. A combination of methods is offered, including a review of academic literature and secondary sources, focus groups, interviews and data extractions from national databases. Findings: The proposed approach is meant to be replicable in different countries, thus allowing for comparison amongst markets. With reference to a specific country and year, the following outputs are provided: market size in terms of the number of players and generated turnover – total and split by LSPs type – and market concentration measures. A practical application of the proposed approach to a specific context, i.e. Italy is finally offered. Originality/value: The study focusses on the logistics outsourcing market and considers financial-reporting data from LSPs, avoiding the need for introducing assumptions about the value of logistics operations for shippers. The proposed approach can contribute to strengthening the accuracy of LSPs' market analyses, and supporting the development of national policies by local governments. The adoption of multiple methods brings rigour and reliability to the study. Finally, high flexibility is ensured, as the method may be adaptable over time to cope with future changes in the logistics landscape.